2006
DOI: 10.1016/j.ejheart.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator‐activated receptor‐α and ‐γ in auricular tissue from heart failure patients

Abstract: Objective: Peroxisome proliferator-activated receptors (PPARs), key transcriptional regulators of lipid and energy metabolism in cardiomyocytes, have recently been proposed to modulate cardiovascular pathophysiological responses in experimental models. However, there is little information about the functional activity of PPARs in human heart failure. Aims: To investigate PPAR-a and -g expression and activity, and the association with ET-1 production and fibrosis, in cardiac biopsies from patients with end-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This is the first study using a well-recognized animal model of heart failure to measure changes in PPAR-γ expression and activity. The data presented here, however, follow well with that observed by Gomez-Garre et al [9]. In their study, the researchers measured PPAR-γ expression in left ventricles of patients with endstage heart failure due to ischemic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is the first study using a well-recognized animal model of heart failure to measure changes in PPAR-γ expression and activity. The data presented here, however, follow well with that observed by Gomez-Garre et al [9]. In their study, the researchers measured PPAR-γ expression in left ventricles of patients with endstage heart failure due to ischemic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the use of glitazones, agents which activate PPAR-γ, are tolerated in all but late stage patients, presumably due to increased fluid retention [16]. It is currently unclear however, how the expression of PPAR-γ as well as its activity is altered with the progression of disease, though recent data has suggested that in human auricular tissue PPAR-γ mRNA and protein expression is increased in patients with ischemic cardiomyopathy [9].…”
Section: Introductionmentioning
confidence: 99%
“…AS160 is a downstream substrate of Akt/PKB that plays a key role in mediating the translocation of GLUT4 to the plasma membrane in response to insulin [21]. It was found that the ability of insulin to stimulate AS160 phosphorylation is impaired in insulin-resistant skeletal muscle, and that this impairment is ameliorated by interventions leading to improved insulin sensitivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro cardiac-hypertrophy model, the PPAR␣ agonists fenofibrate and Wy-14,643 and the PPAR␤/␦ agonist L165041 reduced hypertrophy, although the expression of both PPAR␣ and PPAR␤/␦ were found to be decreased during hypertrophy (108). In contrast, in humans it was observed that protein expression of both PPAR␣ and PPAR␥ were increased in failing left ventricle (109). Cardiomyocyte-specific knockout of PPAR␤/␦ resulted in lipotoxic dilated cardiomyopathy caused by a decreased expression of fatty acid handling genes (110).…”
Section: Polymorphisms and Genetic Alterations Of Ppars And Risk Of Cvdmentioning
confidence: 97%